Financial Leverage of Faculty of Higher Educational Institutions in the Province of Capiz - Joesan D. Borres; Joseph G. Guevarra (Philippine Social Science Journal, 2020)
Faculty-entrepreneurs started their business using savings and personal money.  Over time, with an insufficient amount of capital and to maximize business operation, faculty-entrepreneurs incur debt. Findings on financial literacy, financial capability, financial management, and faculty's financial well-being were very low and negative. So far, there is a dearth of studies that have been conducted on financial leverage, particularly on the faculty who are engaged in business. Financial leverage refers to the source of business capital used in the form of equity and debt. The paper explored the level of financial leverage in terms of equity and debt of faculty of higher educational institutions when they are taken as a whole and grouped according to age, sex, and gross monthly business income. Likewise, it determined the difference in the level of financial leverage in terms of equity and debt when teachers are grouped according to the aforementioned demographics. Also, it explored the relationship between equity and debt.  Likewise, it determined the result of financial leverage in their investment practices.